Automatic Chair Arrangement System using Microcontroller 8082 - Swain, Biswaranjan; Prasad Tripathy, Hara; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
The present paper relates to “Automatic Chair Arrangement Systems”. The idea is taken from technology of self-parking cars, therefore the work can also be titled as "Self-Parking Chair". The framework comprises of microcontroller, RF transmitter switch, and ultrasonic sensor as its major components. The system can be used in offices, schools, colleges etc. The system works on a single click of transmitter switch, and the chair will be directed towards its initial place (default location), resulting in tidy and neat place. The adapted chair system is controlled using an 8052 microcontroller.